Energy storage in grids with high penetration of variable generation. (Asian Development Bank, 2017)
Grid level energy storage is likely to dominate the conversation in the power industry in the coming years, just like renewable energy dominated the conversation in the past 2 decades. This report targets investors, developers, utility planners, power sector policy makers, and readers who wish to understand the role energy storage is likely to play in the smart grid of the future. For developing countries, the report provides an introduction to the necessary technical background on energy storage, the role it is likely to play as penetration of renewable energy increases in the grid, and the policy prescriptions to realize the wide range of benefits of energy storage.